2018
DOI: 10.1177/0892705718805130
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation kinetics of PP/PLA nanocomposite blends

Abstract: In this article, the effect of adding polylactide (PLA) and nanoclay on the thermal stability of polypropylene (PP) films was analyzed using thermogravimetric analysis. The thermal degradation kinetic parameters such as activation energy ( Ea), order of reaction ( n), and frequency factor (ln ( Z)) of the samples were studied over a temperature range of 30–550°C. Analyses were performed under nitrogen atmosphere with four different heating rates (i.e. 5, 10, 15, and 20°C min−1). The Ea was calculated by Kissin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Blending of PLA with other polymers has been extensively analyzed using other biopolymers such as starch [ 4 , 5 , 6 ], polyhydroxyalkanoates (PHA) [ 7 , 8 , 9 ], poly(ε-caprolactone) (PCL) [ 10 , 11 , 12 ], or polybutylene adipate -co- terephthalate (PBAT) [ 13 , 14 , 15 ]. In addition, the effectiveness of blends of PLA with some petroleum-derived commodity plastics such as polyethylene terephthalate (PET) [ 16 , 17 ], polyvinyl chloride (PVC) [ 18 ], thermoplastic elastomers (TPEs) [ 19 , 20 ], polypropylene (PP) [ 21 , 22 ], and polyethylene (PE) [ 23 , 24 , 25 , 26 ] has been reported. Bearing in mind this wide potential of PLA blends, it should be noted that currently, PE can either be obtained from a petrochemical route or a bio-based approach, leading to so-called green polyethylene or bioPE.…”
Section: Introductionmentioning
confidence: 99%
“…Blending of PLA with other polymers has been extensively analyzed using other biopolymers such as starch [ 4 , 5 , 6 ], polyhydroxyalkanoates (PHA) [ 7 , 8 , 9 ], poly(ε-caprolactone) (PCL) [ 10 , 11 , 12 ], or polybutylene adipate -co- terephthalate (PBAT) [ 13 , 14 , 15 ]. In addition, the effectiveness of blends of PLA with some petroleum-derived commodity plastics such as polyethylene terephthalate (PET) [ 16 , 17 ], polyvinyl chloride (PVC) [ 18 ], thermoplastic elastomers (TPEs) [ 19 , 20 ], polypropylene (PP) [ 21 , 22 ], and polyethylene (PE) [ 23 , 24 , 25 , 26 ] has been reported. Bearing in mind this wide potential of PLA blends, it should be noted that currently, PE can either be obtained from a petrochemical route or a bio-based approach, leading to so-called green polyethylene or bioPE.…”
Section: Introductionmentioning
confidence: 99%
“…The Kissinger method is an integral multiple heating rate method that has been widely used in many studies based on ICTAC recommendations. 35,36,38 It predicts a more reliable E a value for the degradation process of a system based on the following relationship 42 :…”
Section: Activation Energy and Thermal Stabilitymentioning
confidence: 99%
“…They also investigated the effect of PLA and nanoclay inclusion on thermal stability and degradation kinetics of PP films. 37 They showed that the activation energy (E a ) value of PP was much higher than that of PLA, whereas the addition of PLA and nanoclay in PP decreased the E a . Moreover, the addition of compatibilizer increased the compatibility and E a of blended films up to some extent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from that, incorporation of nanofiller into the blends also serves a significant impact on the final properties of nanocomposites, such as mechanical, thermal, morphology, and interfacial properties [20][21][22]. In recent years, many papers reported on PLA/PP blends reinforced with clay [23][24], multi-walled carbon nanotubes [25], and sepiolite [26]. However, few studies investigated the effect of graphene nanoplatelet (GNP) reinforced on PLA/PP blends.…”
Section: ■ Introductionmentioning
confidence: 99%